2020
DOI: 10.21203/rs.3.rs-131822/v1
|View full text |Cite|
Preprint
|
Sign up to set email alerts
|

RETRACTED: “From Hell to Healed” – A Qualitative Study on Women’s Experience of Recovery, Relationships and Sexuality after Severe Obstetric Perineal Injury

Abstract: Background: Few studies have investigated women’s experiences of daily life after childbirth complicated by obstetric anal sphincter injury (OASI). The aim of the present study was to explore experiences related to recovery, sexual function, relationships and coping strategies among women affected by OASI. Methods: In-depth interviews were conducted using a purposive sample of 11 women affected by OASI. Women were interviewed 1-2 years after their first childbirth. Inductive qualitative content analysis was ap… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Further, in previous research, women experience insecurities regarding incontinence at work [19], similar to our participants, who described how internalised shame made them hide their condition. Other studies have also found institutionalised objectification [44][45][46], where healthcare professionals normalise persistent morbidities or question the legitimacy of symptoms. The long struggle for adequate healthcare depicted in our study is also supported by others [25,44,47].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, in previous research, women experience insecurities regarding incontinence at work [19], similar to our participants, who described how internalised shame made them hide their condition. Other studies have also found institutionalised objectification [44][45][46], where healthcare professionals normalise persistent morbidities or question the legitimacy of symptoms. The long struggle for adequate healthcare depicted in our study is also supported by others [25,44,47].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have also found institutionalised objectification [44][45][46], where healthcare professionals normalise persistent morbidities or question the legitimacy of symptoms. The long struggle for adequate healthcare depicted in our study is also supported by others [25,44,47]. Hence, previous research shows almost solely adverse effects of SPT on working life.…”
Section: Discussionmentioning
confidence: 99%